2021
DOI: 10.1136/bmjopen-2021-050534
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective cohort analysis of survival of children living with HIV/AIDS in Mumbai, India

Abstract: ObjectivesTo understand the survival in a cohort of children living with HIV/AIDS (CLHAs) and to study the factors associated with survival in CLHAs in government antiretroviral therapy (ART) centres in Mumbai, India.DesignThis is a retrospective cohort analysis.SettingData from electronic ART records of children from 15 ART centres in Mumbai, Maharashtra, India.Participants2224 CLHAs registered in one of these ART centres from 2004 until October 2019. CLHAs up to the age of 18 at the time of registration were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The mortality rate observed in this study aligns with findings from Southwest Ethiopia (11.2 deaths per 1000 child-year observations) [ 18 ], Asia–Pacific (16.5 deaths per 1000 child years) [ 32 ], and the International Maternal Pediatric Adolescent AIDS Clinical Trials (IMPAACT) P1074 multicenter cohort studies in the United States (7 per 1000 child years) [ 33 ]. However, the result indicate a lower mortality rate compared to studies conducted in the Benishangul Gumuz region (54 deaths per 1000 child years) [ 34 ], Northwest Ethiopia (54 deaths per 1000 child years) [ 35 ], referral hospitals of Amhara regional state (44 deaths per 1000 child years) [ 25 ], selected public hospitals of the Addis Ababa city administration (4.98 deaths per 1000 child months) [ 36 ], the government ART centers in Mumbai, India (22.75 deaths per 1000 child years) [ 37 ], and Tanzania (135 per 1000 child years) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate observed in this study aligns with findings from Southwest Ethiopia (11.2 deaths per 1000 child-year observations) [ 18 ], Asia–Pacific (16.5 deaths per 1000 child years) [ 32 ], and the International Maternal Pediatric Adolescent AIDS Clinical Trials (IMPAACT) P1074 multicenter cohort studies in the United States (7 per 1000 child years) [ 33 ]. However, the result indicate a lower mortality rate compared to studies conducted in the Benishangul Gumuz region (54 deaths per 1000 child years) [ 34 ], Northwest Ethiopia (54 deaths per 1000 child years) [ 35 ], referral hospitals of Amhara regional state (44 deaths per 1000 child years) [ 25 ], selected public hospitals of the Addis Ababa city administration (4.98 deaths per 1000 child months) [ 36 ], the government ART centers in Mumbai, India (22.75 deaths per 1000 child years) [ 37 ], and Tanzania (135 per 1000 child years) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate in this study was less than 1 per 100 person-years, and the hazard of death was less than 0.05 during the follow-up. Previous studies on the mortality of children on ART ranged from 1.8 to 2.3 per 100 person-years in Asia and South America [ [12] , [13] , [14] ]. A Retrospective cohort study with a total of 221 children who were initiated on HAART from 2005 to 2009 and followed up until 2013 conducted in Cameroon showed that 9.9% of children (n = 22) died over a follow-up period of 755 child-years (mortality of 2.9 per 100 child-years) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possible reason was that the children or adolescents included in our study were those who survived despite not initiating ART within one year of birth. One retrospective cohort analysis of 2224 children who were registered with the government ART centers in Mumbai from 2004 to 2019 showed that the hazard ratio for mortality was higher in children who registered with the ART center in the first year of life compared with those who in children older than 1 year of age [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Despite the fact that there is a Prevention of Parent to Child Transmission Program in place in India to reduce perinatal transmission, it remains one of the most common routes for HIV transmission. 3 Most children infected by HIV do manifest the initial symptoms before their 1st birthday. In order, to control and treat the symptoms people living with HIV/AIDS (PLHAs) are taken on anti-retroviral therapy (ART), as early diagnosis and initiation of ART reduces the progression of the disease and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Described as the “Epidemic of the Century” each day in 2021, approximately 850 children became infected with HIV 1 and the most recent statistics estimate that India has about 86 000 children living with HIV/AIDS (CLHAs) 2 . Despite the fact that there is a Prevention of Parent to Child Transmission Program in place in India to reduce perinatal transmission, it remains one of the most common routes for HIV transmission 3 . Most children infected by HIV do manifest the initial symptoms before their 1st birthday.…”
Section: Introductionmentioning
confidence: 99%